1998
DOI: 10.1897/1551-5028(1998)017<1620:hampbm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated and Methylsulfonyl Polychlorinated Biphenyl Metabolites in Albatrosses From Midway Atoll, North Pacific Ocean

Abstract: Concentrations of hydroxylated metabolites of polychlorinated biphenyls (PCBs) (OH-PCBs) and methylsulfonyl metabolites of PCBs (MeSO 2 -PCBs) were determined in plasma and liver of albatrosses collected from the Midway Atoll in the central North Pacific Ocean. The mean total concentrations of OH-PCBs in plasma of Laysan albatrosses (Diomedea immutabilis) and black-footed albatrosses (Diomedea nigripes) were 11.5 and 27.1 ng/g wet weight, respectively. Total concentrations of OH-PCBs were only one-to fivefold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 35 publications
12
37
3
Order By: Relevance
“…The distribution of individual OH-PCBs varied geographically (Figure 4). We found 4-OH-CB187 to be a primary OH-PCB metabolite in the maternal blood, consistent with results from other studies (Bergman et al 1994; Fängström et al 2002; Klasson-Wehler et al 1998; Meironyté Guvenius et al 2003; Soechitram et al 2004), whereas Sandau et al (2000) observed 4-OH-CB107 to be a primary congener. Sjödin et al (2000) also determined that 4-OH-CB107 was a primary congener in Baltic Sea fishermen.…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of individual OH-PCBs varied geographically (Figure 4). We found 4-OH-CB187 to be a primary OH-PCB metabolite in the maternal blood, consistent with results from other studies (Bergman et al 1994; Fängström et al 2002; Klasson-Wehler et al 1998; Meironyté Guvenius et al 2003; Soechitram et al 2004), whereas Sandau et al (2000) observed 4-OH-CB107 to be a primary congener. Sjödin et al (2000) also determined that 4-OH-CB107 was a primary congener in Baltic Sea fishermen.…”
Section: Discussionsupporting
confidence: 92%
“…These six congeners were also reported in a survey of hydroxylated phenolic contaminants in lake trout from various Ontario lakes [10], and from rainbow trout exposed to a mixture of PCBs in the laboratory [41]. Studies in humans, polar bears, seals, and birds have also reported a dominance of penta-to heptachlorinated hydroxylated homologs and the presence of specific congeners similar to those detected in the present study [8,9,12]. However, the identified congeners represented only approximately 17% of penta-OH-PCBs, 84% of tetra-OH-PCBs, and 88% of hexa-OH-PCBs at Wheatley Harbour, but 100% of tetra-, penta-, and hexa-OH-PCBs in Hillman Marsh.…”
Section: Plasma Hydroxylated Pcbssupporting
confidence: 84%
“…Four of these congeners were also reported in the plasma of benthic fish species from the Detroit River, at concentrations as high as 65 ng/g for 3 0 -OH-CB138 [11]. Metabolites reported in the present study have also been noted in marine birds and mammals [9,[12][13][14]32]. Studies in humans, polar bears, seals, and birds have also reported a dominance of penta-to heptachlorinated hydroxylated homologs and the presence of specific congeners similar to those detected in the present study [8,9,12].…”
Section: Plasma Hydroxylated Pcbssupporting
confidence: 68%
See 1 more Smart Citation
“…In a former report, the levels of 4OH-CB107, 4OH-CB146, and 4OH-CB187 in the liver samples of harbor seals [23] and in the blood samples of gray seals [13] were higher than what we found. The potential parent PCBs of 4′OH-PCB107 and 4OH-CB101/4OH-CB120 are CB105, CB118, and CB101, respectively [14,15,18,35,36]. In the blubbers of Baikal seals, the concentration of CB101 was three orders of magnitude higher than those of CB105 and CB118, indicating that the concentration profiles of the metabolites reflected those of the corresponding parent PCBs.…”
Section: Application To Liver and Brain Samplesmentioning
confidence: 96%